2020
DOI: 10.3390/w12072004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical and Isotopic Assessment of Groundwater in the Goda Mountains Range System. Republic of Djibouti (Horn of Africa)

Abstract: The hydrogeological system of the Goda Mountains Range (GMR) in the Republic of Djibouti (Horn of Africa), hosted by volcanic and sedimentary formations, is the only water resource in the Tadjourah region for more than 85,000 inhabitants. Water needs are expected to drastically increase in the coming years, due to fast socio-economic development of the region. Accordingly, this system is under high pressure and should sustainably be exploited. However, little is known about the hydrogeology of this system. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…With this background, groundwater studies in Djibouti have been intensified in recent years with respect to groundwater quality, age, and flow systems. In Tadjoura area, the northern part of the country, previous study using stable isotope and radioisotope analyses to estimate groundwater recharge systems and ages [2]. The results indicate that the groundwater in the area is mixed with different geological formations, such as rhyolite, basalt, and alluvium, indicating that the area may have a complex hydrogeological system.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…With this background, groundwater studies in Djibouti have been intensified in recent years with respect to groundwater quality, age, and flow systems. In Tadjoura area, the northern part of the country, previous study using stable isotope and radioisotope analyses to estimate groundwater recharge systems and ages [2]. The results indicate that the groundwater in the area is mixed with different geological formations, such as rhyolite, basalt, and alluvium, indicating that the area may have a complex hydrogeological system.…”
Section: Introductionmentioning
confidence: 90%
“…150 mm yr-1 ), in this region and only occurs irregularly short-time localized rainfall. Hence, rivers are not formed regularly in this region, and groundwater has been used as the main water resource for humans and livestock [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of d-excess varies due to evaporation at various stages [28]. The use of stable isotopes can be extremely useful in identifying various hydrological processes [6,29]; mechanisms [11]; sources [21,30]; characteristics of surface-groundwater interactions [22]; and depth-wise salinity variations [19] in India. In view of the above, the present study is carried out to (i) assess the present-day waterlogging and groundwater saline in aquifers at different depths in the southwest (SW) parts of Punjab and (ii) identify depth-wise saline water and freshwater zones in the aquifers using isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…According to Scanlon et al [12] and Singh et al [13], there is no universal approach to study groundwater recharge and that is why the amount of methods reported in scientific literature is high. Amongst these methods, it can be highlighted: (i) the ones based on measuring the water table level [14][15][16]; (ii) the ones that use chemical tracers [17][18][19][20][21]; (iii) the ones based on direct Regardless of the issue, the intention, for the most part, is to provide tools for information gathering, in a way that water management may be more rational and efficient. According to Bortolin et al [1], for surface water a lot has been accomplished in that sense, but there is still a huge gap to bridge when it comes to groundwater.…”
Section: Introductionmentioning
confidence: 99%